Finite Element Based Fatigue Life Prediction of Cylinder Head for Two-Stroke Linear Engine Using Stress-Life Approach - M. M., Rahman; M. M., Noor; R. A., Bakar; M. A., Maleque; A. K., Ariffin (Asian Network for Scientific Information, 2008)
This study describes the finite element based fatigue life prediction of cylinder head for a two-stroke free piston linear engine subjected to variable amplitude loading, applicable to electric power generation. A set of aluminum alloys, cast iron and forged steel for cylinder head are considered in this study. The finite element modeling and analysis were performed utilizing the finite element analysis codes. The fatigue life analysis was carried out using finite element based fatigue analysis commercial codes. Fatigue stress-life approach was used when the piston is subjected to variable amplitude at different loading conditions. The effects of mean stress and sensitivity analysis on fatigue life are discussed. From the results, it was shown that the Goodman mean stress correction method is predicted more conservative (minimum life) results. It was found to differ significantly the compressive and tensile mean stresses. The compressive mean stress are beneficial however tensile mean stress detrimental to the fatigue life. The effect of materials and components S-N was also investigated and not found to give any large advantages, however the effect of certainty of survival was found to give noticeable advantages and it concluded that the 99.9% are fond to be design criteria. The proposed technique is capable of determining premature products failure phenomena.